Study of E-Waste and Its Effect on Health and Environment (International Journal of Scientific Research in Science and Technology, 2024)
In this present paper, electronic waste encompassing a range of obsolete electronic devices such as computers, telecommunication devices, home appliances, recording devices, and automobile components is ever-growing resulting in the deterioration of environmental quality. Countries like India suffer not only due to the generation of their electronic wastes but also from the dumping of such wastes from developed countries. Consumers find it convenient to buy a new computer rather than to upgrade the old one due to the changing configuration and technology. The components of electronic wastes result in toxicity and carcinogenicity. Some of them include lead, mercury, cadmium, tin, copper, silicon, beryllium, aluminum, and Polychlorinated Biphenyls.